TLR5-deficiency controls dendritic cell subset development in an autoimmune diabetes-susceptible model - Pearson, James Alexander; Hu, Youjia; Peng, Jian; Wong, F. Susan; Wen, Li (Frontiers in Immunology, 2024)
The incidence of type 1 diabetes (T1D), an autoimmune disease, has been increasing worldwide and recent studies have shown that the gut microbiota are associated with modulating susceptibility to T1D. Toll-like receptor 5 (TLR5) recognizes bacterial flagellin and is widely expressed on many cells, including dendritic cells (DCs), which are potent antigen-presenting cells (APCs). TLR5 modulates susceptibility to obesity and alters metabolism through gut microbiota; however, little is known about the role TLR5 plays in autoimmunity, especially in T1D. To fill this knowledge gap, we generated a TLR5-deficient non-obese diabetic (NOD) mouse, an animal model of human T1D. Here, we found that TLR5-deficiency led to a reduction in CD11c+ DC development in utero, prior to microbial colonization, which was maintained into adulthood. This was associated with a bias in the DC populations expressing CD103, with or without CD8α co-expression, and hyper-secretion of different cytokines, both in vitro (after stimulation) and directly ex vivo. We also found that TLR5-deficient DCs were able to promote polyclonal and islet antigen-specific CD4+ T cell proliferation and proinflammatory cytokine secretion. Interestingly, only older TLR5-deficient NOD mice had a greater risk of developing spontaneous T1D compared to wild-type mice. In summary, our data show that TLR5 modulates DC development and enhances cytokine secretion and diabetogenic CD4+ T cell responses. Further investigation into the role of TLR5 in DC development and autoimmune diabetes may give additional insights into the pathogenesis of Type 1 diabetes.